Urbanization and Quality of Life: A Comprehensive Literature - Rameli, Norizan; Ramli, Fariha; Salleh, Dani (Journal of Social Transformation and Regional Development, 2020)
Urbanization is a process that affects economic and social development of developing countries. The urbanization processes arisen not only comprises the issue of migration among the residents, but also involves the social environment transformations of the people in the city. Urban evolution has a positive and negative impact on urban residents. Malaysian life quality index assesses the level of income, physical well-being, psychology and social, health, safety, housing, education, environment, culture and recreation, transportation and communication. Urbanization and quality of life exhibits an ongoing structure to achieve sustainable development. Despite this, emphasis still needs to be given on equality, fairness and freedom in pursuing the quality of social life in the city